Variation of the Twilight Stages due to Sun Elevation: A Case Study in Malaysia - Yasser A. Abdel-Hadi; A. H. Hassan (New Trends in Physical Science Research Vol. 4, 2022)
The main objective of this study is to determine the exact time of beginning both of the True (Real) Dawn and the True (Real) Dusk within the twilight intervals. The True Dawn begins at that time at which the white thread of diffused solar radiation appears on the eastern horizon. On the other hand, the Real Dusk begins at that time at which the white thread of diffused solar radiation disappears on the western horizon. Determining both of these times is very important for Muslims, since they are times of morning (Fajr) and evening (Esha’) prayers in Islam. So, this study is concerned with determining the altitude of the sun under the horizon to according to which both of the mentioned signs occurs. The Sky Quality Meter (SQM) was used to assess the brightness at night, pseudo dawn, true dawn, true dusk, and pseudo dusk in four Malaysian regions in 2007 and 2008. The measurements were made when the device was oriented to the position of sunrise and sunset at the horizontal angle of the sunrise or sunset and at five degrees just above horizon during the entire monitoring period. The altitude of the sun for the true dusk was found to be -14.38±0.91 and for the begin of the pseudo dusk was found to be -14.86º±0.91 and the end of the pseudo dusk is -17.8±0.7, while for the beginning of the true dawn it was found to be-14.19±0.52 (for high confidence -14.71) and for the pseudo dawn was found to be -18.62±0.82. The light magnitude of the full night after the pseudo dusk was found to be 20.77±0.93 mag./arcsec², while it was found to be 22.17 ± 0.1 mag./arcsec² before the pseudo dawn. These results agree with many previous researches in this field and lead to adopt new values of the sun vertical depression angle for the True Dawn (between 14.7 and 15) and for the True Dusk (between 15 and 15.5).